Efficacy of Very Low Dose Inhaled Corticosteroid And Reduction of Misuse of Antibiotics and Hospital Admission in Infants and Toddlers With Recurrent Wheezy Chest - Mazumder, Pradip Kishore; Mallick, Pranab Kanti; Dutta, Arup (Journal of Chittagong Medical College Teachers’ Association, 2017)
Background: Wheeze in infants and toddlers are a common symptom and sign. Inhaled Corticosteroids are considered the most effective treatment available for long-term control of asthma or recurrent wheezing of children. The aim of the present study was to see the efficacy of very low dose inhaled Beclomethasone in reducing the misuse of antibiotics and hospital admission among the infants and toddlers with recurrent wheezing. Materials and methods: This was a prospective study done among 70 infants and toddlers of 4months to 3 years of age having a recurrent wheeze. Open -ended questionnaires were used. All patients were studied with Beclomethasone Dipropionate HFA inhaler 1puff (50 micrograms) twice daily and Salbutamol inhaler 1-2 puffs (Each puff contain 100 micrograms) 3 to 4 times daily when needed via small volume spacer with a mask. Sixty patients completed the study for total 3 months and were included in the analysis. Patients were followed up every 4 weeks interval and symptoms, use of antibiotics and need for hospital admission all were calculated. Data were analyzed by SPSS 20. Results: Among the 70 patients, persistent wheezing was present in 7.1% cases, recurrent cough was present in 21.4% cases and recurrent wheezing was present in 71.4% cases. 14.2% cases had a family history of asthma and 85.8% had no such family history. Among 60 patients those completed the study, day cough and day wheezing were reduced to 30(50%) and 5(8.3%) respectively following the first month of low dose ICS therapy. Day cough and day wheezing were reduced to 10(16.6%) and 1(1.6%) after 2 months and after 3 months these were reduced to 1(1.6%) and 0% respectively. Night cough and night wheeze were reduced to 40(66.6%) and 20(33.3%) respectively after the first month of ICS therapy. After 2nd month these were reduced to 15(25%) and 5(8.3%) and after 3rd month these were 2(3.3%) and 0% respectively. Antibiotics received before initiation of ICS therapy 100% (n=70) and after initiation of ICS therapy was 16.6% (n=60). Hospital admission rate before initiation of ICS therapy was 66.66% (n=70) and after ICS therapy was 8.33% (n=60). Both hospital admission and need of antibiotics were reduced after the initiation of low dose ICS therapy which was statistically significant (p<0.01). Conclusion: Our study has shown the improvement in symptoms and also decreases the use of antibiotics and reduces the frequency of hospitalization following treatment with low dose Inhaled Corticosteroid. JCMCTA 2017 ; 28 (1) : 8 - 12